Political opportunities, not migration flows: why the EU cooperates more broadly on migration with some neighbouring states. - Stutz, Philipp (Journal of Ethnic & Migration Studies, 2023)
Why is the EU cooperating more on migration issues with some third countries than others? What explains this variation? In recent years, the EU has intensified its institutionalised cooperation with third countries in the area of migration, although to different degrees. The extent of migration cooperation is measured in this article by conducting a fuzzy-set Qualitative Comparative Analysis. It looks at the conditions that have triggered more or less cooperation in 23 countries of the Eastern and Southern EU neighbourhood up to 2015, a key moment in the external relations. Theoretically, the article draws on five factors to explain the different levels of cooperation: (1) migration flows; (2) the state of democracy in the partner country; (3) existing relations with the EU; (4) economic dependence of the partner country on the EU; (5) administrative capacities of the partner country. The article advances the argument that a third country's existing relations with the EU or the state of democracy in combination with a high level of economic dependence on the EU are the key factors for understanding why some third countries cooperate more. The number of migrants originating from or transiting through a third country is only of secondary importance.